Simulations of the anisotropy of friction force between a silicon tip and a substrate at nanoscale. (September 2013) - Chen, Lihuan; Wang, Yufeng; Bu, Hao; Chen, Yunfei
In this article, the anisotropy of the friction force with a variety of rotation angles between a silicon tip and a substrate was investigated using molecular dynamics simulations. When the silicon tip slides over the silicon substrate under incommensurate contacting surfaces, the results of the simulations illustrate that the sliding friction forces decrease with the increase of the rotation angle from 0° to 45° and increase with the increase of the rotation angle from 45° to 90°. Furthermore, an approximate symmetrical curve of the friction force for the 45° angle can be obtained, and the friction force is minimum and close to superlubricity at the 45° angle. However, at the same angle, the friction force stops decreasing with the increase of the temperature and its magnitude depends mainly on the degree of the commensurability of the contacting surfaces rather than the temperature.